Pengaruh Relaksasi Benson terhadap Kecemasan Pasien Pre Op dengan Ulkus Diabetikum di Ruang Instalasi Bedah Sentral (IBS): The Effect of Benson Relaxation on Preoperative Anxiety among Patients with Diabetic Ulcers in the Surgery Central Installation - Sri Wijayanti; Feri Catur Yuliani; Yeni Rusyani (Jurnal Keperawatan Berbudaya Sehat, 2026)
Diabetic ulcers, a complication of diabetes mellitus, often require surgery, which triggers significant anxiety in patients. Preoperative anxiety can negatively impact the patient's physiological and psychological stability. Benson relaxation is a non-pharmacological intervention proven to reduce anxiety. The goal of this study to determine the effect of Benson relaxation on preoperative anxiety levels in patients with diabetic ulcers in the IBS ward at Fastabiq Sehat Hospital, PKU Muhammadiyah Pati. This was a quantitative study with a quasi-experimental design using a one-group pretest-posttest approach. A sample of 33 respondents was selected using a purposive sampling technique. Anxiety data were measured using the HARS and analyzed using the Wilcoxon test. Before the intervention, the majority of patients experienced moderate (51.5%) and severe (48.5%) anxiety. After Benson relaxation, mild anxiety increased to 54.5%. The Wilcoxon test showed a p-value of 0.000 (p < 0.05). Benson Relaxation is effective in reducing preoperative anxiety in patients with diabetic ulcers and can be implemented in preoperative nursing care